Labour, carcerality and punishment: 'Less-than-human' labour landscapes. (December 2020) - Cassidy, Kathryn; Griffin, Paul; Wray, Felicity
This paper brings together carceral and labour geographies to highlight new research avenues and empirical gaps. Despite valuable engagements with unfree and precarious work by labour geographers and substantial developments within carceral geography around carceral circuitry and intimate economies of detention, punitive aspects of work remain largely under-theorised within labour geography, while the political economy of carceral labour is relatively side-lined within carceral geography. The paper calls for two interrelated research agendas – the first a punitive labour geographies agenda, and the second a more sustained political economy lens applied to carceral geography in the context of labour and work.